PENTINGNYA SOSIALISASI MENJAGA KESEHATAN MENTAL BAGI REMAJA GUNA MENINGKATKAN KESADARAN AKAN MASALAH KESEHATAN MENTAL DI MASA PANDEMI DI DESA WONOJOYO (KKN-DR IAIN KEDIRI) - Kumala, Siti Al Wasi'u (Insan Cita : Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract :Mental health is a prosperous condition in which individuals can use cognition skills and functional emotions in their community and fulfill their daily needs. Individuals can maximize their potential to manage stress and anxiety. COVID-19 is a virus that attacks the human respiratory and emerges in Wuhan, China for the first time, then spreading widely to whole countries. The emerge of the COVID-19 pandemic causes the new habit and certainly, it can affect mental health, mainly for adolescents where it’s the unstable phase and they could not control their emotions well. The socialization about the importance of maintaining mental health conducted to adolescents in Wonojoyo Village, Gurah, Kediri through community service programs showed that adolescents were aware and more concerned about the importance of maintaining mental health. Maintaining mental health can make adolescents have good mental health and bring positive thoughts and prevent disease.Keywords : covid-19, mental health, adolescents, pandemicAbstrak :Kesehatan mental adalah kondisi sejahtera dimana individu dapat memanfaatkan kemampuan kognisi dan emosi yang berfungsi dalam komunitasnya, dan memenuhi kebutuhan hidupnya sehari-hari serta dimana individu bisa memaksimalkan potensinya untuk mengelola stress dan kecemasan pada dirinya sendiri. Covid-19 adalah virus yang menyerang pernafasan dan pertama kali muncul di Wuhan, China dan menyebar hingga ke berbagai Negara. Dengan adanya pandemic COVID-19 terdapat banyak kebiasaan baru, dan tentunya hal ini bisa mempengaruhi kesehatan mental, terutama bagi remaja dimana remaja adalah usia yang masih labil dan belum